Guidance for producing a Campbell evidence and gap map. Issue 4 (19th November 2020) - White, Howard; Albers, Bianca; Gaarder, Marie; Kornør, Hege; Littell, Julia; Marshall, Zack; Mathew, Christine; Pigott, Terri; Snilstveit, Birte; Waddington, Hugh; Welch, Vivian
Abstract: Evidence and Gap Maps (EGMs) are a systematic evidence synthesis product which display the available evidence relevant to a specific research question. EGMs are produced following the same principles as a systematic reviews, that is: specify a PICOS, a comprehensive search, screening against explicit inclusion and exclusion criteria, and systematic coding, analysis and reporting. This paper provides guidance on producing EGMs for publication in Campbell Systematic Reviews.